2023
DOI: 10.3390/life13020315
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Arbuscular Mycorrhizal Fungi Enhances Terpene Synthase Expression in Salvia rosmarinus Cultivars

Abstract: Culinary herbs are commercially cultivated for their wide range of volatile compounds that give characteristic aromas and tastes. Rosemary (Salvia rosmarinus Spenn.) is an excellent model for assessment of methods improvement of volatile production as cultivars offer a wide variety of aromatic profiles due to the large family of terpene synthase genes. Arbuscular mycorrhizal fungi (AMF) associations have been shown to improve essential oil production in aromatic plants and offer one approach to enhance aroma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…This study not only confirmed the in vivo function of LeBAHD1 in the biosynthesis of acetylshikonin but also provided new insights into the biosynthetic pathway of shikonin and its derivatives. In another study on improving essential oil production in aromatic plants, Devlin's group found that the addition of Arbuscular Mycorrhizal Fungi (AMF) profoundly influenced terpene synthase expression in six rosemary cultivars without impacting plant growth [12]. Their findings demonstrated the potential for the use of AMF in the improvement of aroma in culinary herbs within a commercial setting.…”
mentioning
confidence: 99%
“…This study not only confirmed the in vivo function of LeBAHD1 in the biosynthesis of acetylshikonin but also provided new insights into the biosynthetic pathway of shikonin and its derivatives. In another study on improving essential oil production in aromatic plants, Devlin's group found that the addition of Arbuscular Mycorrhizal Fungi (AMF) profoundly influenced terpene synthase expression in six rosemary cultivars without impacting plant growth [12]. Their findings demonstrated the potential for the use of AMF in the improvement of aroma in culinary herbs within a commercial setting.…”
mentioning
confidence: 99%